2015
DOI: 10.1016/j.gaitpost.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Using horizontal heel displacement to identify heel strike instants in normal gait

Abstract: Heel strike instants are an important component of gait analyses, yet accurate detection can be difficult without a force plate. This paper presents two novel techniques for kinematic heel strike instant (kHSI) detection which examined maximal resultant horizontal heel displacement (HHD). Each of these HHD techniques calculates HHD from a selected reference location of either the stance ankle or stance heel to the swing heel. The proposed techniques, along with other previously established techniques, were val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The algorithm was validated in Zeni et al [40]. Therefore, it was considered a valid approach for the detection of IC and TC and was employed in this study rather than an alternative approach [43].…”
Section: Discussionmentioning
confidence: 99%
“…The algorithm was validated in Zeni et al [40]. Therefore, it was considered a valid approach for the detection of IC and TC and was employed in this study rather than an alternative approach [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although this is a simple procedure, it does not always yield similar results to those using actual gait events across all gait speeds and subjects when detecting toe-off. In order to achieve better accuracy, the trajectory of the horizontal ankle position (x-coordinate of the ankle) in relation to the hip was determined using a forward kinematic model to detect gait events [17, 25, 26] and the results were compared to the data obtained using a force plate treadmill (Supplementary Materials). Similar to other studies that have used 3-D camera systems [17, 25, 26], we found that the horizontal ankle position during gait could serve as an accurate surrogate method to define stance and swing phases of gait cycles (Supplementary Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, the features were also calculated based on the OMC data, also segmented to 100% GC. In this case the IC was estimated based on the markers placed on the heel, toe and the pelvis and a custom written Matlab (Mathworks Inc., Natick, MA, USA) script incorporating an approach based on [50,51]. Here, feature Set 1 and 2 counted 1937 samples per feature (1404 labeled “healthy”, aka Control Group; 533 labeled “patient”, aka THA Group).…”
Section: Methodsmentioning
confidence: 99%